2017
DOI: 10.3389/fmech.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

SOPHIA: Soft Orthotic Physiotherapy Hand Interactive Aid

Abstract: This work describes the design, fabrication, and initial testing of a Soft Orthotic Physiotherapy Hand Interactive Aid (SOPHIA) for stroke rehabilitation. SOPHIA consists of (1) a soft robotic exoskeleton, (2) a microcontroller-based control system driven by a brain-machine interface (BMI), and (3) a sensorized glove for passive rehabilitation. In contrast to other rehabilitation devices, SOPHIA is the first modular prototype of a rehabilitation system that is capable of three tasks: aiding extension based ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 55 publications
0
24
0
2
Order By: Relevance
“…Even though pneumatic actuation is heavily utilized in the field of soft robotics, the use of sensory feedback is still in its nascent stage. [197][198][199] To improve the combination of pneumatic actuators with stretchable strain sensors, a sensorized actuated glove has been developed to perform accurate finger kinematics with dexterity and control for rehabilitation applications. [200] In a similar study, Cheng et al demonstrated a pneumatic actuator with the capability of the bending angle monitoring using a hydrogel-based stretchable strain sensor (Figure 13b).…”
Section: Soft Robotics and Neuromechanicsmentioning
confidence: 99%
“…Even though pneumatic actuation is heavily utilized in the field of soft robotics, the use of sensory feedback is still in its nascent stage. [197][198][199] To improve the combination of pneumatic actuators with stretchable strain sensors, a sensorized actuated glove has been developed to perform accurate finger kinematics with dexterity and control for rehabilitation applications. [200] In a similar study, Cheng et al demonstrated a pneumatic actuator with the capability of the bending angle monitoring using a hydrogel-based stretchable strain sensor (Figure 13b).…”
Section: Soft Robotics and Neuromechanicsmentioning
confidence: 99%
“…[26,103] In the area of rehabilitation, patients exhibiting reduction in sensation (e.g., as the result of stroke or injury) may benefit from the use of kinesthetic devices. [103,104] Most types of kinesthetic appliances are non-portable, which require placing the hands in bulky stirrups or take the form of gloves with large inflatable pneumatic attachments with their attendant pumps. [105][106][107][108] In this work, we developed a wearable, highly portable, composite of a textile and acrylic thermoplastic in a glove in which the stiffness could be changed by heating and cooling with embedded thermoelectric devices.…”
Section: Kinesthetic Simulation Using Organic Materialsmentioning
confidence: 99%
“…Relacionado a lo anterior, SOPHIA (Soft Orthotic Physiotherapy Hand Interactive Aid) es un sistema de rehabilitación mediante extensión asistida, que monitorea los ejercicios del paciente y guia pasivamente el procedimiento, el cual puede ser usado de manera eficiente en pruebas clínicas futuras (McConnell et al, 2017).…”
Section: Aplicaciones Del Aprendizaje Automático En La Medicina Físicunclassified